Creating Social Change Through Creativity Anti-Oppressive Arts-Based Research Methodologies (Springer International Publishing, 2018)
This book examines research using anti-oppressive, arts-based methods to promote social change in oppressed and marginalized communities. The contributors discuss literary techniques, performance, visual art, and new media in relation to the co-construction of knowledge and positionality, reflexivity, data representation, community building and engagement, and pedagogy. The contributors to this volume hail from a wide array of disciplines, including sociology, social work, community psychology, anthropology, performing arts, education, medicine, and public health.